Erratum: Kinematic Detections of Protoplanets: A Doppler Flip in the Disk of Hd 100546 (Astrophysical Journal Letters 2019 883 l41 Doi: 10.3847/2041-8213/Ab4425) - Perez-Marquez, S (Institute of Physics Publishing, 2019)
The definition of the disk rotation curve, labeled as v˜f (r) in the published article, is ambiguous with respect to the projection factor sin(i?), where i0 is the average disk inclination. The first sentence of the last paragraph in Section 1, should be replaced by “The rotation curve of a disk, (Formula Presented) in cylindrical coordinates, and where i0 is the average disk inclination, represents the mass-averaged tangential velocity in the plane of the disk as a function of radius.” Likewise, the rotation curve is readily comparable with the Keplerian velocity profile via (Formula Presented) so Equation (11) in the last paragraph of Section 3.1 should be updated to (Formula Presented) The numbers in the published article are not affected as the numerical implementation is consistent with this updated definition of v˜0. © 2019, The American Astronomical Society. All rights reserved..